Web Impact Factor for Malaysian Public Universities - Abdul Arif; Ismail, N. A (International Journal of Future Computer and Communication, 2013)
This paper evaluates Public Universities in Malaysia based on the webometric perspective. Web Impact Factor (WIF) evaluation was carried out by using Majestic SEO and Google Search engine. It is found that UMS have the highest Average WIF with 13.013 followed by UMK with 2.670 WIF and in the third place is UPNM with 1.289 WIF.